Insulin and bull sperm interactions during cryopreservation - N. Tekin ÖNDER; Taygun GÖKDEMIR; Muhammet Can KILIÇ; Oğuzhan ŞAHIN; Savaş YILDIZ; Cihan KAÇAR; Murat Can DEMİR; Yavuz ÖZTÜRKLER (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2023)
The aim of the present study was to evaluate the effects of insulin supplemented extender on bull semen at a post-thaw stage. Semen samples were collected four times from a Zavot bull which is endangered species in Türkiye. Semen samples were diluted with Tris based extender supplemented with 10 IU or 15 IU of insulin and control. Motility and plasma membrane integrity were evaluated by a phase-contrast microscope. Acrosome integrity (Fitc-Peanut Agglutinin), mitochondrial membrane potential (Rhodamine 123), nitric oxide level (4,5-Diaminofluorescein-2/diacetate) were evaluated with dual staining propidium iodide using flow cytometry. Motility and plasma membrane functional integrity were better preserved compared to control group (P<0.05). Acrosome integrity results were statistically similar between control and 10 IU insulin groups (P>0.05), but increased insulin negatively affected acrosome integrity (p<0.05). Mitochondrial membrane potential was found to be higher when compared all cells in insulin containing groups compared to control (P<0.05). However, results were found similar in all groups with PI negative/mitochondrial membrane potential positive (P>0.05). There were not any significant differences among groups in terms of nitric oxide level (P>0.05). In conclusion, it was thought that insulin involved in energy metabolism and improved preservation of bull semen.